2020
DOI: 10.1186/s42826-020-00042-4
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish as an alternative animal model in human and animal vaccination research

Abstract: Much of medical research relies on animal models to deepen knowledge of the causes of animal and human diseases, as well as to enable the development of innovative therapies. Despite rodents being the most widely used research model worldwide, in recent decades, the use of the zebrafish (Danio rerio) model has exponentially been adopted among the scientific community. This is because such a small tropical freshwater teleost fish has crucial genetic, anatomical and physiological homology with mammals. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 96 publications
0
41
0
1
Order By: Relevance
“…Despite this, teleosts produce only three classes of antibodies: IgM 61 , IgW 62 , and IgZ, the latter exclusive to zebrafish 63 . Studies in zebrafish showed that in the regions of the BCR receptor were targets of mutations 5 . Although the affinity of antibodies in ectothermic vertebrates is less efficient than in mammals, the deaminase activation and affinity maturation might contribute to the diversification of antibodies in zebrafish 64,65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, teleosts produce only three classes of antibodies: IgM 61 , IgW 62 , and IgZ, the latter exclusive to zebrafish 63 . Studies in zebrafish showed that in the regions of the BCR receptor were targets of mutations 5 . Although the affinity of antibodies in ectothermic vertebrates is less efficient than in mammals, the deaminase activation and affinity maturation might contribute to the diversification of antibodies in zebrafish 64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between zebrafish and human genomes revealed remarkable sequence and functional conservation of 70% genetic similarity to humans 3,4 . Zebrafish have been used as a model to study the safety of vaccines 5 and to assess toxicology that could be correlated to human health 6,7 . Recently, the WHO (2020) prepared a document on all vaccine candidates for COVID-19 clinical trials, reporting 35 candidate vaccines in the clinical evaluation and at least 166 vaccine candidates in preclinical and clinical development.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the presence in fish of innate and adaptive immunity elements assists research in infectious processes, being susceptible to infectious by gram-negative and gram-positive bacteria, protozoa, viruses, fungi, and mycobacterium. Advancements in unique cloning, mutagenesis, and transgenesis techniques allowed identifying a significant number of mutants (Bailone et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…De acordo com Bailone et al (2020b), o emprego do Zebrafish como modelo para o desenvolvimento de vacinas de uso veterinário não está restrito ao âmbito de organismos aquáticos, mas também do desenvolvimento de vacinas com agentes etiológicos que acometem outras espécies de animais, como é o caso da tuberculose, na qual o modelo Zebrafish tem sido empregado para a identificação pré-clínica de antígenos de vacinas (OKSANEN et al, 2013;MYLLYMÄKI et al, 2018).…”
Section: B) Uso Do Modelo Zebrafish Em Pesquisas Na áRea De Medicina unclassified